2023
DOI: 10.1007/s11934-023-01184-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential of AI-Driven Chatbots in Urology: Revolutionizing Patient Care Through Artificial Intelligence

Ali Talyshinskii,
Nithesh Naik,
B. M. Zeeshan Hameed
et al.

Abstract: Purpose of Review Artificial intelligence (AI) chatbots have emerged as a potential tool to transform urology by improving patient care and physician efficiency. With an emphasis on their potential advantages and drawbacks, this literature review offers a thorough assessment of the state of AI-driven chatbots in urology today. Recent Findings The capacity of AI-driven chatbots in urology to give patients individualized and timely medical advice is one of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is interesting but perhaps not surprising that none of this was ever mentioned by patients. There are many areas that health care professionals need to stay up to date on such as artificial intelligence and new simulation methods, staying up to date with social media and its impact on health care is yet another new field ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting but perhaps not surprising that none of this was ever mentioned by patients. There are many areas that health care professionals need to stay up to date on such as artificial intelligence and new simulation methods, staying up to date with social media and its impact on health care is yet another new field ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer education has been one of the areas in which the implementation of chatbots has had the most significant impact on urological cancer patients, as it offers remote, easily accessible for some patients, help that can be programmed to answer questions about treatment, surgical procedures, emotional support, and above all 24-hour availability, allowing the patient also to take control of their health and contribute positively to the discussion about their cancer, as well as to the discussion of their condition [24]. Studies such as Allen et al (2023) have shown that the use of this type of AI has multiple benefits in patients since 62% of the participants found the application very good, significantly increased their percentage of general knowledge of the disease, clarified many doubts about the treatment they were receiving, increased by 86% the confidence and expertise with which they make decisions about their treatment and can have much more constructive discussions with their treating urologist, making more efficient control appointments and improving doctor-patient communication [11].…”
Section: Use Of Chatbots In Urology Education Psychosocial Support An...mentioning
confidence: 99%
“…There are many identified benefits of applying this type of AI to patients. The versatility and programming possibilities of these systems make their applications in the context of the management of an oncological patient many and propose an alternative not only in treatment but also palliative care, helping the companion or family to prevent diseases by focusing and helping to identify risk factors associated with it [1,24]. (Figure 2)…”
Section: Use Of Chatbots In Urology Education Psychosocial Support An...mentioning
confidence: 99%
“…The role of AI expands to various benign and malignant conditions such as urolithiasis, benign prostate enlargement (BPH), paediatric urology, renal transplant, urogynaecology, robotic surgery, and uro-oncology pertaining to prostate, kidney, bladder and prostate [ 5 8 ]. Our editorial reviews the broad role of AI in urology for diagnosis and risk assessment, treatment planning and precision medicine, robotic surgery and AI-assisted procedures, improved patient care and outcomes, challenges and ethical considerations, and its future role within urology [ 9 , 10 , 11 ].…”
mentioning
confidence: 99%